The Role of the Tourism Village Communication Forum in the Development of Tourism Villages in Sleman Regency, Indonesia - Suharsa, Junaidi; Suryani, Dewi Amanatun (Jurnal Pemerintahan dan Kebijakan (JPK), 2026)
The growth of tourism villages in Sleman Regency has posed significant challenges to the Tourism Office's effective guidance and development. The Tourism Village Communication Forum (Forkom Deswita) has emerged as an alternative, bringing together various stakeholders to enable more effective, targeted tourism development. This research aims to examine and analyze Forkom Deswita's role in the development of tourism villages in Sleman Regency. We used a descriptive qualitative method, gathering data through interviews and field observations. Based on Ife & Tesoriero's role theory (facilitator, educator, technical, representative), our findings indicate that Forkom Deswita has been effective in its facilitation and education roles. It is particularly evident in strengthening institutional capacity and enhancing human resource capabilities within the tourism villages. However, its technical role in partnerships and representative role in promotion still need optimization to encourage a wider variety of attractions and broader marketing efforts. This research contributes to understanding strategies for strengthening local tourism institutions and has important implications for formulating more synergistic and sustainable tourism village development policies in the future.